Preparation of monolayer hollow spherical tungsten oxide films with enhanced near infrared electrochromic performances. (20th February 2019) - Zhang, Xiang; Dou, Shuliang; Li, Wenjie; Wang, Lebin; Qu, Huiying; Chen, Xi; Zhang, Leipeng; Zhao, Yingming; Zhao, Jiupeng; Li, Yao
Abstract: In this study, monolayer hollow spherical tungsten oxide (WO3 ) films have been prepared for the first time by magnetron sputtering combined with the colloidal crystal template method. Due to the large specific surface area, short ion diffusion distances, and weak scattering of the monolayer hollow structure, the hollow spherical WO3 film exhibits excellent electrochromic performance. This includes high transmittance modulation in the near-infrared spectral range (78.8% at λ = 1000 nm), fast switching response time (2.41 s for coloration and 1.28 s for bleaching), and high coloring efficiency (102.9 cm 2  C −1 ) at 1000 nm. The results show that the hollow spherical WO3 film can effectively regulate incident light, especially in the near infrared band, which is not visible but has significant thermal effects. Graphical abstract: Image 1 Highlights: Hollow spherical WO3 films were prepared by magnetron sputtering method. Spherical structure was arranged in a single layer. Hollow spherical WO3 films have an enhanced electrochromic performance.